Shelterbelt shading reduces aggregate stability in cultivated mollisols: Evidence from a field experiment - Yu Li; Yu Fu; Jinzhong Xu; Yupeng Zhang; Hanzhe Lei; Xiaoya Zhang; Weibin Zhao; En Ci (CATENA, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

NiFeS4/Ni3S4/NiS multiphase sulfides integrated with carbon nanotubes for efficient and high-performance electrode in cobalt-free rechargeable zinc–air batteries: A demonstration of rare compounds by an interrupted chemical reaction - Noto Susanto Gultom; Ji-En Liu; Celca Rahmatunnisa; Yen-Fu Chen; En-chi Chang; Dong-Hau Kuo (Chemical Engineering Journal, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Quantitative scattering analysis of rough surface based on the boundary scattering matrix - Yang-pu Chen; Li-Yun Fu; Qing-qing Li; Hong-en Li; Qing-he Meng (Applied Geophysics, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Study on the thermal insulation efficiency and ecological conservation effects of intelligent sustainable green walls - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; You-En Zhong; Zhi-Jia Feng (Energy and Buildings, 2026)

Dual-functional Cu2O-Fe3O4 Fenton nanocatalyst integrating pollutant degradation and magnetic microplastic separation in wastewater treatment - Hong En Fu; Yeonbeom Kim; Seung Won Kang; Young Jun Jang; Bum Chul Park; Young Keun Kim (Chemical Engineering Journal, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Comprehensive Geophysical Characteristics and Exploration Significance of the Xiarihamu Super-Large Copper-Nickel Deposit in the East Kunlun Metallogenic Belt - Ji-en Dong; Bao-chun Li; Tao Wang; Yu-long Li; Xiao-jun Dong; Fu-chun Wang; Hai-kui Tong; Zhen-hua Zheng; Hua Li; Peng Wang (Applied Geophysics, 2025)

Dry cleaning of food-grade plastics on a gas-solid biphase fluidized bed: Efficiency, assessment and mechanism - Ziyang Liu; Cong-Cong Zhang; Fu-Shen Zhang; Shi-Lei Han; Dai-En Yang (Journal of Environmental Chemical Engineering, 2025)

Highly selective and sensitive detection of β-lactam antibiotics in food samples using a fluorescent turn-on probe based on metal-organic framework - Ran An; Rui-Xuan Li; Xin Shang; Chang-Qi Fu; En-Qing Gao; Qi Yue (Food Chemistry, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Eutrophication‐induced dinoflagellate succession contributes to marine carbon sequestration through refractory dissolved organic matter accumulation - Fu‐Tao Fang; Zhuo‐Yi Zhu; Yuan‐Bi Yi; Ding He; Hong‐Yan Bao; En‐Ren Zhang; Cheng‐Xu Zhou (Limnology and Oceanography, 2025)
The increasing eutrophication of coastal seas is causing a shift in the most important phytoplankton groups from diatoms to dinoflagellates, but its feedback to marine carbon cycling remains unclear. Here, we investigated the potential of the key coastal phytoplankton, the diatom Skeletonema costatum , and the dinoflagellate Prorocentrum donghaiense , for refractory dissolved organic carbon (DOC) accumulation over dark degradation incubations of 70 d. Our multi‐method approach showed that dinoflagellate detritus, rather than diatom detritus, significantly contributes to refractory DOC. This is evidenced by the fact that the detritus of dinoflagellates compared to that of diatoms (1) has a weaker transmittance in infrared spectrometry, indicating a lower content of labile organic substances (alcohol and amide groups); (2) has a higher release and/or transformation efficiency of particulate organic carbon to DOC (81% vs. 50%); (3) has a lower content of labile fraction, amino acid (8% vs. 17% carbon) and exhibits lower degradability of the DOC formed (23% vs. 30%); (4) has a lower content of labile compounds determined by Fourier transform ion cyclotron resonance mass spectrometry (maximum molecular lability boundary: 21% vs. 31%); and (5) has a higher proportion of refractory carboxylic‐rich alicyclic molecules (57% ± 0.5% vs. 51% ± 0.7%) over incubations. Our results emphasize that eutrophication‐triggered coastal dinoflagellate succession has a significant potential for positive feedback to carbon sequestration through the formation of refractory DOC.

The evolution of sulfur during coalification in marine land interaction environments based on the sequential extraction of different sulfur species - Shuangxue Du; En Long; Yu Qi; Yiwen Ju; Pan Wu; Yong Fu; Shangyi Gu; Hao Zhang; Qingguang Li (Marine and Petroleum Geology, 2025)

Impact of future climate from different general circulation models on cotton yield predictions in north Cotton Belt through crop simulation with DSSAT - Mohil Pourebrahimi Foumani; Xinhua Yin; Joshua S. Fu; Cheng-En Yang; Regina Adotey (Field Crops Research, 2025)

Determining representative elementary volume for hydraulic conductivity of fractured rock masses: Comparative analytical and numerical studies - Tai-Sheng Liou; Jia-Jing Lin; Po-Kai Chen; En-Chao Yeh; Fu-Shu Jeng; Tai-Tien Wang (Engineering Geology, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

Acceptability of a Fresh Produce Intervention for Individuals With Serious Mental Illnesses - Gabriella Farland; Leah G. Pope; En Fu; Dana Cohen; Cheryl Gerstler; Merrill Rotter; Michael T. Compton (Journal of Nutrition Education and Behavior, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Temporal dynamics of the microbial heterogeneity–diversity relationship in microcosmic systems - Wei Deng; Nong-En Bai; Fu-Liang Qi; Xiao-Yan Yang; Rong She; Wen Xiao (Oecologia, 2024)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Sedimentary organic molecular compositions reveal the influence of glacier retreat on ecology on the Tibetan Plateau - Siwei Shi; Hai Xu; Yong Shui; Dandan Liu; Qiaorong Xie; Kang'en Zhou; Jin Zhang; Yunping Song; Jing Wang; Chukun Hu; Yuchun Wang; Pingqing Fu (Science of The Total Environment, 2023)

Can the mix-charged NF membrane directly obtained by the interfacial polymerization of PIP and TMC? - Qiu-Yu Zhu; Zi-Yun Xu; Jie-Han Fu; Jie Huang; Zhen-Liang Xu; Min Tong; En-Chao Li; Yong-Jian Tang (Desalination, 2023)

Sedimentary organic matter molecular composition reveals the eutrophication of the past 500 years in Lake Daihai, Inner Mongolia - Chukun Hu; Hai Xu; Siwei Shi; Jianghu Lan; Kang'en Zhou; Jin Zhang; Yunping Song; Jing Wang; Pingqing Fu (Environmental Research, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Nonclimacteric ripening characteristics of ‘Jen-Ju Bar’ guava conferred by a defect in the expression of the system-2 ACC synthase gene PgACS1 - Kuo-En Chen; You-Fu Liu; Yu-Chang Liu; Margo Sulistio; Chyi-Chuann Chen; Chun-Ta Wu (Postharvest Biology and Technology, 2023)

Home-Use and Real-Time Sleep-Staging System Based on Eye Masks and Mobile Devices with a Deep Learning Model - Tsung-Hao Hsieh; Meng-Hsuan Liu; Chin-En Kuo; Yung-Hung Wang; Sheng-Fu Liang (Journal of Medical and Biological Engineering, 2021)

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

Multi-hole joint acquisition of a 3D-RVSP in a karst area: Case study in the Wulunshan Coal Field, China - Ming-Shun Hu; Dong-Ming Pan; Fu-Bao Zhou; Juan-Juan Li; Yang-Zhou Wang; Shen-En Chen; Yong-Zhong Xu (Applied Geophysics, 2020)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

The tectono-magmatic evolution of the West Junggar terrane (NW China) unravelled by U–Pb ages of detrital zircons in modern river sands - Bo Liu; Bao-Fu Han; En-Pu Gong; Jia-Fu Chen (International Geology Review, 2019)

An inversion of transient electromagnetic data from a conical source - Hai-Yan Yang; Feng-Ping Li; Shen-En Chen; Jian-Hua Yue; Fu-Sheng Guo; Xiao Chen; Hua Zhang (Applied Geophysics, 2018)

IR Spectra of Different O2-Content Hemoglobin from Computational Study: Promising Detector of Hemoglobin Variant in Medical Diagnosis - Su-qin Zhou; Tu-nan Chen; Guang-fu Ji; En-ren Wang (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Constitutive expression of a plant ferredoxin-like protein (pflp) enhances capacity of photosynthetic carbon assimilation in rice (Oryza sativa) - Hsiang Chang; Hsiang-En Huang; Chin-Fu Cheng; Mei-Hsuan Ho; Mang-Jye Ger (Transgenic Research, 2017)

Effectiveness of SO2 emission control policy on power plants in the Yangtze River Delta, China—post-assessment of the 11th Five-Year Plan - Jiani Tan; Joshua S. Fu; Kan Huang; Cheng-En Yang; Guoshun Zhuang; Jian Sun (Environmental Science and Pollution Research, 2017)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Distinctive Mesorhizobium populations associated with Cicer arietinum L. in alkaline soils of Xinjiang, China - Jun Jie Zhang; Kai Lou; Xiang Jin; Pei Hong Mao; En Tao Wang; Chang Fu Tian; Xin Hua Sui; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2012)

Enhancing phosphorus availability in phosphorus-fertilized zones by reducing phosphate adsorbed on ferrihydrite using rice straw-derived biochar - Hao-Jie Cui; Ming Kuang Wang; Ming-Lai Fu; En Ci (Journal of Soils and Sediments, 2011)

The Impact of Dietary Iodine Intake on Lipid Metabolism in Mice - Shu-Jun Zhao; Yan Ye; Fu-Jun Sun; En-Jiang Tian; Zu-Pei Chen (Biological Trace Element Research, 2011)

A large indel mutation of the bovine ADD1/SREBP1c gene and its effects on growth traits in some native cattle breeds from China - Yong-Zhen Huang; En-Ping Zhang; Jing Wang; Yong-Tao Huai; Liang Ma; Fu-Ying Chen; Xian-Yong Lan; Chu-Zhao Lei; Xing-Tang Fang; Ju-Qiang Wang; Hong Chen (Molecular Biology Reports, 2011)

Temporal patterns of net soil N mineralization and nitrification through secondary succession in the subtropical forests of eastern China - En-Rong Yan; Xi-Hua Wang; Ming Guo; Qiang Zhong; Wu Zhou; Yong-Fu Li (Plant and Soil, 2009)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Genetic diversity of rhizobia associated with Vicia faba in three ecological regions of China - Chang Fu Tian; En Tao Wang; Tian Xu Han; Xin Hua Sui; Wen Xin Chen (Archives of Microbiology, 2007)

Characterization of symbiotic and endophytic bacteria isolated from root nodules of herbaceous legumes grown in Qinghai–Tibet plateau and in other zones of China - Feng Ling Kan; Zhong Yi Chen; En Tao Wang; Chang Fu Tian; Xin Hua Sui; Wen Xin Chen (Archives of Microbiology, 2007)

Biology and life history of Dabry's sturgeon, Acipenser dabryanus, in the Yangtze River - Ping Zhuang; Fu'en Ke; Qiwei Wei; Xuefu He; Yuji Cen (Environmental Biology of Fishes, 1997)

Biology, fisheries, and conservation of sturgeons and paddlefish in China - Qiwei Wei; Fu'en Ke; Jueming Zhang; Ping Zhuang; Junde Luo; Rueqiong Zhou; Wenhua Yang (Environmental Biology of Fishes, 1997)